2012
DOI: 10.1002/hed.22003
|View full text |Cite
|
Sign up to set email alerts
|

Voice outcomes after concurrent chemoradiotherapy for advanced nonlaryngeal head and neck cancer: A prospective study

Abstract: To the best of our knowledge, this is the first prospective study to show that chemoradiation therapy for nonlaryngeal head and neck cancer has a significant effect on the patients' self-reported voice quality, even in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
2
19
1
4
Order By: Relevance
“…The fourth theme to emerge from the interviews related to the comments made by both HNC survivors and carers regarding the necessary adaptations required to adjust and cope with the communication changes (Table 5) Consistent with previous research, the HNC survivors in the current study reported ongoing changes to their speech, voice, and hearing which persisted for months and years post-treatment (Lazarus et al, 2014;Paleri et al, 2012;Swore Fletcher et al, 2012). Though these changes to the communication sub-systems did actually not preclude them from communicating and socialising, the changes made communicating more difficult.…”
Section: Theme 4: Adaptations As a Results Of Communication Changessupporting
confidence: 78%
See 2 more Smart Citations
“…The fourth theme to emerge from the interviews related to the comments made by both HNC survivors and carers regarding the necessary adaptations required to adjust and cope with the communication changes (Table 5) Consistent with previous research, the HNC survivors in the current study reported ongoing changes to their speech, voice, and hearing which persisted for months and years post-treatment (Lazarus et al, 2014;Paleri et al, 2012;Swore Fletcher et al, 2012). Though these changes to the communication sub-systems did actually not preclude them from communicating and socialising, the changes made communicating more difficult.…”
Section: Theme 4: Adaptations As a Results Of Communication Changessupporting
confidence: 78%
“…At present however, relatively little is known about voice and speech outcomes following treatment for non-glottic cancers (Fung et al, 2001;Hamdan et al, 2009;Paleri et al, 2012). In the only known prospective study of voice outcomes following non-surgical management in non-glottic HNC, chemoradiotherapy was shown to have a significant effect on HNC survivors' self-reported vocal function, as rated on the Voice Symptom Scale (VoiSS; Deary, Wilson, Carding, & MacKenzie, 2003), up to 12 months post-treatment (Paleri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With transoral approaches, one can expect a much lower tracheostomy rate, shorter time to decannulation when one is placed and a shorter hospitalization [22 && ,24 && ]. In one study of voice following CRT, there was significant and progressive deterioration of patient perception of vocal quality with follow-up over 2 years [25]. In comparison, most reports on CRT for oropharyngeal cancer do not report tracheostomy rates nor vocal outcomes.…”
Section: Functional Outcomesmentioning
confidence: 99%
“…Vocal impairment following radiation therapy in nonlaryngeal head and neck cancer patients has been widely documented . These negative changes are noted in the perceptual, acoustic, and aerodynamic measures, as well as the voice‐related quality of life of these cancer survivors . However, literature on vocal rehabilitation for the head and neck cancer population only focused on the laryngeal cancer survivors .…”
Section: Introductionmentioning
confidence: 99%